2018
DOI: 10.1142/s0218202518500276
|View full text |Cite
|
Sign up to set email alerts
|

An analytical framework for consensus-based global optimization method

Abstract: In this paper we provide an analytical framework for investigating the efficiency of a consensus-based model for tackling global optimization problems. This work justifies the optimization algorithm in the mean-field sense showing the convergence to the global minimizer for a large class of functions. Theoretical results on consensus estimates are then illustrated by numerical simulations where variants of the method including nonlinear diffusion are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
204
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 110 publications
(210 citation statements)
references
References 35 publications
6
204
0
Order By: Relevance
“…We note that the presence of v f makes the Fokker-Planck equation nonlinear and nonlocal in both the convection and diffusion part. This is nonstandard in the literature and raises several analytical and numerical questions [13].…”
Section: A Consensus-based Optimization (Cbo) Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the presence of v f makes the Fokker-Planck equation nonlinear and nonlocal in both the convection and diffusion part. This is nonstandard in the literature and raises several analytical and numerical questions [13].…”
Section: A Consensus-based Optimization (Cbo) Algorithmmentioning
confidence: 99%
“…Despite its simplicity, we will argue that the algorithm performs surprisingly well and allows for an analytical treatment as the system possesses a mean-field limit towards a partial differential equation (cf. [13]).…”
Section: A Consensus-based Optimization (Cbo) Algorithmmentioning
confidence: 99%
“…The main advantages of the scheme are: it allows for a formal passage to the mean-field limit and hence a rigorous analysis on the PDE level. Indeed, there is a convergence analysis, that indicates a good behavior of the particle scheme, available [3]. The updates of the particle states are based on a comparison to an averaged state.…”
Section: Consensus-based Global Optimizationmentioning
confidence: 99%
“…CBO allows for passage to the mean-field limit resulting in a nonlocal, degenerate, parabolic PDE. Exploiting tools from PDE analysis, it is possible to rigorously prove convergence results for the algorithm (see [3]). In the present article we discuss numerical results obtained with the Particle Swarm Optimization (PSO) [4], Wind-Driven Optimization (WDO) [6] and CBO and show that CBO leads to very competitive results.…”
mentioning
confidence: 99%
“…Later, it was even shown that special classes of singular interaction potentials allow passing to the mean-field limit [5,26]. Nowadays, particle games are also employed in the field of global optimization [16,34].…”
Section: Introductionmentioning
confidence: 99%